# Conjunction elimination

In propositional logic, conjunction elimination (also called and elimination, ∧ elimination,[1] or simplification)[2][3][4] is a valid immediate inference, argument form and rule of inference which makes the inference that, if the conjunction A and B is true, then A is true, and B is true. The rule makes it possible to shorten longer proofs by deriving one of the conjuncts of a conjunction on a line by itself.

An example in English:

It's raining and it's pouring.
Therefore it's raining.

The rule consists of two separate sub-rules, which can be expressed in formal language as:

$\frac{P \land Q}{\therefore P}$

and

$\frac{P \land Q}{\therefore Q}$

The two sub-rules together mean that, whenever an instance of "$P \land Q$" appears on a line of a proof, either "$P$" or "$Q$" can be placed on a subsequent line by itself. The above example in English is an application of the first sub-rule.

## Formal notation

The conjunction elimination sub-rules may be written in sequent notation:

$(P \land Q) \vdash P$

and

$(P \land Q) \vdash Q$

where $\vdash$ is a metalogical symbol meaning that $P$ is a syntactic consequence of $P \land Q$ and $Q$ is also a syntactic consequence of $P \land Q$ in logical system;

and expressed as truth-functional tautologies or theorems of propositional logic:

$(P \land Q) \to P$

and

$(P \land Q) \to Q$

where $P$ and $Q$ are propositions expressed in some formal system.

## References

1. David A. Duffy (1991). Principles of Automated Theorem Proving. New York: Wiley.<templatestyles src="Module:Citation/CS1/styles.css"></templatestyles> Sect.3.1.2.1, p.46
2. Copi and Cohen[citation needed]
3. Moore and Parker[citation needed]
4. Hurley[citation needed]

sv:Matematiskt uttryck#Förenkling